Antiviral defense against Cypovirus 1 (Reoviridae) infection in the silkworm, Bombyx mori. Issue 3 (10th September 2019) - Swevers, Luc; Feng, Min; Ren, Feifei; Sun, Jingchen
Abstract: Recent years have shown a large increase in studies of infection of the silkworm ( Bombyx mori ) with Cypovirus 1 (previously designated as B. mori cytoplasmic polyhedrosis virus), that causes serious damage in sericulture. Cypovirus 1 has a single‐layered capsid that encapsulates a segmented double‐strand RNA (dsRNA) genome which are attractive features for the establishment of a biotechnological platform for the production of specialized gene silencing agents, either as recombinant viruses or as viral‐like particles with nonreplicative dsRNA cargo. For both combatting viral disease and application of Cypovirus‐based pest control, however, a better understanding is needed of the innate immune response caused by Cypovirus infection of the midgut of lepidopteran larvae. Studies of deep sequencing of viral small RNAs have indicated the importance of the RNA interference pathway in the control of Cypovirus infection although many functional aspects still need to be elucidated and conclusive evidence is lacking. A considerable number of transcriptome studies were carried out that revealed a complex response that hitherto remains uncharacterized because of a dearth in functional studies. Also, the uptake mechanism of Cypovirus by the midgut cells remains unclarified because of contrasting mechanisms revealed by electron microscopy and functional studies. The field will benefit from an increase in functional studies that will depend on transgenic silkworm technology and reverse genetics systems for Cypovirus 1. Abstract : An overview is presented of the current knowledge of the immune response against the silkworm pathogen Cypovirus, characterized by a segmented double‐strand RNA genome. Knowledge of the antiviral defense against Cypovirus will determine strategies for more efficient control of the pathogen. Similarly, the antiviral defense mechanism will affect the efficiency by which Cypovirus or derived viral‐like particles can trigger RNA interference effects in the silkworm.